Pembangunan Sistem Inventory Berbasis Website pada Toko Lancar Abadi - Immanuel, Nathanael; Ziveria, Mira (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
In this research. Researchers will take a problem still experienced by many entrepreneurs who are just starting or have been running for a long time. An inventory system sometimes it is often underestimated by entrepreneurs, In addition to functioning to see a list of stock items, The inventory system can also be used as a notification if the stock of an item will run out or less than the amount already determined, The researchers will analyze what kind of inventory system is in accordance by the needs of the lancar abadi store. The goal expected by the research is to be able to assist the store in managing data . The final result of this research is an inventory system can manage the data of lancar abadi